Clival chordomas: A pathological, surgical, and radiotherapeutic review. Issue 6 (4th October 2013) - Fernandez–Miranda, Juan C.; Gardner, Paul A.; Snyderman, Carl H.; Devaney, Kenneth O.; Mendenhall, William M.; Suárez, Carlos; Rinaldo, Alessandra; Ferlito, Alfio; Eisele, David W.
Abstract Background The purpose of this study was to discuss the optimal management of patients with clival chordomas and provide an up‐to‐date review of the field. Methods A schematic description of the anatomy of the clivus and its surrounding structures is provided based on the modular classification of the surgical corridors used in endoscopic skull base surgery. Postoperative radiotherapy (RT) techniques are described. Results The optimal treatment is gross total resection. Recent advances in endoscopic endonasal skull base surgery have allowed very high rates of macroscopic and radiographic complete tumor resection in spite of the challenging location of these lesions. When the tumor location or extension is too lateral or inferior to be effectively resected with an endoscopic approach, an open approach or a combination of endoscopic and open approaches in stages should be considered. Postoperative RT is usually indicated because the likelihood of recurrence is high in spite of complete surgical resection. The main site of recurrence is local and late recurrences are relatively common. The probability of cure is approximately 50% at 10 years and significantly increases when complete tumor resection has been achieved. Conclusion The preferred treatment for patients with clival chordoma is gross total resection (via endoscopic endonasal surgery when possible) followed by postoperative RT. Treatment at experienced multidisciplinary cranial base centers is key to minimize complications and to enhance the probability of total removal of the tumors. © 2013 Wiley Periodicals, Inc. Head Neck 36: 892–906, 2014